PENGELOLAAN COMMUNITY DEVELOPMENT PROGRAM PADA UMKM “KAMPUNG KULINER PUJASERA ENERGI” - Ni Putu Limarandani; AA Ketut Patera; Lasmery RM Girsang (MULIA (Jurnal Pengabdian kepada Masyarakat), 2023)
The community development program is one of the activity agendas that must be owned by large companies, as well as state-owned enterprises, including Pertamina. In this article, the team implementing community service activities synergizes with industry to make a real scientific contribution among community groups. The MSME 'Culinary Pujasera Energi Village' located in Tambakharjo Village (Semarang) is the target for public service. In practice, MSMEs, which were formed in 2019, has now become a means of actualizing and developing home industries (namely culinary businesses) which have shown an increase in the economy for MSME players. Carrying out cooperation with various stakeholders, MSMEs continue to experience business development in the culinary field in line with increased capacity building for active MSMEs actors.